Modification Of Coso Internal Control For The Economy Of Indonesian Corn Emblems SMEs - Kariyoto, Kariyoto; Tibyani, Tibyani (Journal of Innovation and Applied Technology, 2023)
This study aims to determine the application of raw material control and internal support according to COSO and COSO modifications for Micro, Small and Medium Enterprises (MSMEs). The object under study is the Nusantara Corn Chips SMEs. The research method used in this study is a qualitative method with the type of case study. Based on observations, it is known that the internal control of raw materials and supporting ingredients for Nusantara corn chips is still very simple. Based on the survey, it shows that in the control of raw and supporting materials at Emping Jagung Nusantara, there are 10 principles that are appropriate and 7 that are not in accordance with the COSO internal control components. In accordance with this, there are several principles that are not relevant for MSMEs, such as the absence of a board or audit committee as a supervisor for MSMEs Emping Jagung Nusantara. The above basis is irrelevant and takes into account the principles of cost and benefit, the principles of COSO, so that COSO internal controls are formed for MSMEs.